Avaliação das patologias e da biodeterioração na Biblioteca Central da UFSM - Pereira, Luciana Manzoni (2012)
Agents climatic, biological and human action are the main responsible for deterioration of historic buildings, thus the growing concern with the preservation and maintenance of these buildings. This study was conducted at the Central Library Manuel Marques de Souza - Conde de Porto Alegre, located at the Federal University of Santa Maria and its main objective is to identify fungal contamination at the site, which has been a cause of biodeterioration incident in the building. For this work were discussed theoretical frameworks relevant to the subject, photographic surveys, as well as the use of a methodology aimed at collecting fungi, serving as a subsidy for the identification and characterization of microorganisms that are biodeteriorando the building. This was followed by a graphical representation of the pathologies of the building, through maps Damage. After the identification and evaluation of biological agents that cause biodeteriorações that are hitting the building, the data were tabulated to assess the fungal contamination of the Central Library UFSM, which can cause deterioration and also cause disease in users and occupants of that environment.